Evaluation of nurses’ knowledge and practices regarding safety measures beyond intravenous therapy administration in 2024 - Abdulazizmaiod almalki,; Oashjaber salim,; Ahlam Saad Abdullah Alshehri,; Abeer Ayied alotaibi,; Amani Abdullah Ahmed,; Nisreen Abdullah Alshamrani,; Aisha Mohammed Ali Salhabi,; Kalthoml Brahim khardaliy,; Hossam Ali Ateeq Al-Harbi,; Faez Muhayl Khalaf Alqurashi,; Salma Huzaymwasel aldajani,; Saad Mohammed O Alharthi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Medication errors are found all around the world, putting patients and medical professionals at risk for adverse outcomes linked to blood birth. However, unsafe intravenous (IV) injection practices have proliferated globally, indicating the need for nurses to administer IV therapy safely and effectively in order to avoid major mistakes, risks, and consequences. Aim of the study: evaluate nurses' knowledge and practices related to safety measures during administration of intravenous therapy. Setting: This study was carried out in Makkah Hospital, Saudi Arabia in medical units. Subject: All staff nurses involved in direct patient care and responsible for giving IV therapy and work in medical units (65) nurses. Tools: Tool 1: Nurses’ knowledge related to safety measures during administration of intravenous therapy; through a structured interview schedule. Tool 2: Nurses’ practices observational checklist related to safety measures during administration of IV therapy. Result: All nurses were female, majority of them in age group of > 35 years. Where, 70.8% and 67.7% of the nurses; respectively had poor total practices and knowledge scores related to their safety nursing measures during IV therapy administration. Additionally, a positive statistical correlation was found between total nurses 'knowledge scores and total nurses practice scores. Conclusion: The present study nurses’ practices as well as their knowledge levels as regards to safety measures during the administration of IV therapy were poor. On the other hand, a positive statistically correlation was observed between total nurses' knowledge and practice scores reflecting that their performance is mainly based on their acquired knowledge. Recommendation: Nurses should be encouraged to attend regular scientific meetings, conferences and training programs to keep pace with the rapidly growing knowledge and practical in nursing science.